Rastro atrás no caminho labiríntico da memória - Marchezan, Luiz Gonzaga [UNESP] (My University, 2012)
The literary subject of Jorge Andrade’s Rasto atrás and Labirinto, a drama and a novel, respectively, focuses on the author’s memory, the repository of a subjectivity that gathers the results of a tense relationship between the author and his father along their family history. This motif, transformed into an imaginary solution in both narratives, is studied here on literary grounds

Rasto atrás (1965) e Labirinto (1978), respectivamente, drama e romance de Jorge Andrade (1922-1984), têm sua matéria literária concentrada na memória do autor, reduto de uma subjetividade que reúne os resultados de uma tensa relação do ficcionista com o pai, no interior de uma história familiar. É esse motivo, transfigurado em solução imaginária nas duas narrativas, que estudamos literariamente.
The labyrinthine way of memory
Keywords: Drama; Novel; Memory; Autobiography; Drama; Romance; Memória; Autobiografia